Composition of Skipjack Tuna (Katsuwonus pelamis L) Taken by Commercial Fishery from the Northeastern Waters of Indonesia - R. Sala (Marine Science Department Diponegoro University, 2009)
The objectives of this study are to detect the changes in size composition of skipjack tuna, and to examine any association that may exist between skipjack tuna and other tunas taken from the northeastern Indonesian waters. Data were collected through a field survey by taken samples of catch of commercial fisheries in the study areas. Results of the study revealed that size composition of skipjack taken by pole-and-liners tended to be stable over the observation periods and was dominated by size class larger than 2.5 kg. However, there was a tendency of domination of skipjack for size class less than 1 kg, particularly taken by Bitung’s purse-seiners fishing around North Sulawesi water. It was also revealed that skipjack taken by the commercial fishery show a strong association with other tuna, especially yellowfin tuna. Key words : skipjack, size composition, commercial fishery, northeastern waters of Indonesia Penelitian ini bertujuan untuk mengevaluasi perubahan komposisi ukuran cakalang yang tertangkap dan asosiasi yang mungkin ada antara cakalang dan tuna yang lain pada hasil tangkapan di kawasan utara perairan Indonesia bagian timur. Data penelitian ini diperoleh melalui survey lapangan dengan mengambil sampel hasil tangkapan dari perikanan komersial di lokasi penelitian. Dari hasil penelitian ini terungkap bahwa komposisi ukuran cakalang yang tertangkap oleh huhate (pole-and-liner) cenderung stabil dan didominasi oleh ukuran lebih besar dari 2,5 kg. Akan tetapi untuk cakalang yang tertangkap oleh pukat cincin didominasi oleh ukuran yang kurang dari 1 kg, terutama yang tertangkap di perairan sekitar Sulawersi Utara. Hasil penelitian ini juga mendapatkan adanya korelasi yang erat antara ikan cakalang dan tuna ekor kuning yang tertangkap oleh perikanan komersial. Kata kunci : cakalang, komposisi ukuran, perikanan komersial, perairan bagian utara kawasan timur Indonesia.